DIGITAL PARADISE: NAVIGATING THE COMPLEXITY OF TAXATION IN THE ERA OF TECHNOLOGICAL TRANSFORMATION - M. Yusuf Bahtiar; Eko Sudarmanto; Sulfianty (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The digital revolution has fundamentally transformed the taxation landscape, necessitating a nuanced understanding of its implications for fiscal governance. This research literature review thoroughly examines the multifaceted dimensions of taxation in the era of technological transformation, drawing insights from a diverse array of scholarly literature, policy documents, and empirical studies. Key themes explored encompass tax governance mechanisms, regulatory responses to cross-border tax evasion and profit shifting, compliance behaviors, and the redistributive impact of taxation in the digital age. By synthesizing existing research, this review provides a holistic understanding of the complexities of navigating contemporary fiscal governance's digital paradise. The literature synthesis reveals the critical role of tax governance mechanisms in addressing the challenges the digital economy poses. Regulatory responses, including proposals for digital taxation frameworks and international tax cooperation agreements, are examined to elucidate their potential efficacy in fostering tax compliance and mitigating tax evasion and avoidance. Furthermore, the review delves into the intricate interplay between taxpayer motivations, compliance drivers, and communication strategies, offering insights into enhancing tax compliance behaviors in the digital era. Additionally, the redistributive effects of taxation policies are analyzed, highlighting their role in addressing income inequality and promoting social equity in digitally-driven economies. This review contributes to the scholarly discourse by providing a comprehensive analysis of taxation in the digital age, offering valuable insights for policymakers, scholars, and practitioners. By unpacking the complexities of taxation amidst technological transformation, it informs efforts to devise effective fiscal policies that promote fairness, efficiency, and sustainability in the digital era.